PENGARUH PEMBERIAN AROMATERAPI LEMON TERHADAP EMESIS GRAVIDARUM PADA IBU HAMIL TRIMESTER I DI DESA SUNGAI PUTIH WILAYAH KERJA PUSKESMAS PANTAI CERMIN KABUPATEN KAMPAR - Sri Wahyuni; Komaria Susanti; Lisviarose Lisviarose; Hirza Rahmita (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Pregnant women in the first trimester are at risk of experiencing emesis gravidarum which can endanger the mother and fetus. Treatment can be done with non-pharmacological methods such as lemon aromatherapy. Data from the Pantai Cermin Health Center UPT, in Sungai Putih Village there are 41.7% of high-risk pregnant women, including those experiencing hyperemesis gravidarum. The study aims to determine the effect of giving lemon aromatherapy on emesis gravidarum in first trimester pregnant women in Sungai Putih Village, Pantai Cermin Health Center Working Area, Kampar Regency. This type of research is quantitative with a quasi-experimental approach with one group pre-test and post-test. The population is 62 pregnant women, a sample of 16 respondents. Sampling uses a purposive sampling technique. The research instrument is a questionnaire. Data are analyzed using a dependent T test. The results of the study, before giving lemon aromatherapy, the majority of respondents experienced moderate emesis gravidarum, as many as 81.3%. After giving lemon aromatherapy, the majority of respondents experienced mild emesis gravidarum, as many as 87.5%. There is an effect of lemon aromatherapy on emesis gravidarum in pregnant women in the first trimester (ρ = 0.000). It is recommended that community health centers use lemon aromatherapy as part of their maternal health services, particularly as a non-pharmacological intervention to manage emesis gravidarum in the first trimesterKeywords: Lemon Aromatherapy, Emesis Gravidarum, Pregnant Women